Skin‐to‐skin contact is associated with earlier breastfeeding attainment in preterm infants. (17th May 2016) - Oras, Paola; Thernström Blomqvist, Ylva; Hedberg Nyqvist, Kerstin; Gradin, Maria; Rubertsson, Christine; Hellström‐Westas, Lena; Funkquist, Eva‐Lotta
Abstract: Aim: This study investigated the effects of skin‐to‐skin contact on breastfeeding attainment, duration and infant growth in preterm infants, as this has not been sufficiently explored. Methods: A prospective longitudinal study on Kangaroo mother care was carried out, comprising 104 infants with a gestational age of 28 + 0 to 33 + 6 and followed up to one year of corrected age. Parents and staff recorded the duration of skin‐to skin contact during the stay in the neonatal intensive care unit (NICU). Medical data were collected through patient records, and follow‐up questionnaires were filled in by parents. Results: The 53 infants who attained full breastfeeding in the NICU did so at a median (range) of 35 + 0 (32 + 1 to 37 + 5) weeks of postmenstrual age, and skin‐to‐skin contact was the only factor that influenced earlier attainment in the regression analysis ( R 2 0.215 p < 0.001). The daily duration of skin‐to‐skin contact during the stay in the NICU did not affect the duration of breastfeeding or infant growth after discharge. Furthermore, infant growth was not affected by the feeding strategy of exclusive, partial breastfeeding or no breastfeeding. Conclusion: A longer daily duration of skin‐to‐skin contact in the NICU was associated with earlier attainment of exclusive breastfeeding. Abstract :